Telomerase Activity as a Marker for Differential Diagnosis of Pancreatic Adenocarcinoma: A Systematic Review and Meta-Analysis. Issue 2 (April 2016) - Gu, Huajian; Xin, Xiaoyan; Pan, Yaozhen; Zhang, Hong; Tian, She; Sun, Chengyi
Background: Studies evaluating the role of telomerase activity in pancreatic adenocarcinoma are inconsistent and a systemic review of the available literature may shed new light on this issue. Objective: To systematically review the usefulness of telomerase activity in distinguishing pancreatic cancer from other pancreatic diseases. Methods: A comprehensive search of the PubMed and Embase databases was conducted to identify eligible studies. Only studies evaluating telomerase activity in patients with suspected or previously diagnosed pancreatic adenocarcinomas versus nonpancreatic adenocarcinomas and published in English with a sufficient number of cases were included. The hierarchical summary receiver operating characteristic (HSROC) model was used to establish the potential value of telomerase activity in the diagnosis of pancreatic adenocarcinoma. Results: A total of 19 studies qualified for this meta-analysis. In distinguishing pancreatic adenocarcinoma from benign diseases, the pooled sensitivity and specificity of telomerase activity were 0.81 (95% CI, 0.68-0.90) and 0.97 (95% CI, 0.93-0.98), respectively; the diagnostic odds ratio (DOR) was 126.62 (95% CI, 49.94-320.99); beta was −1.16 (95% CI, −3.62-1.29), Z was −0.93, p was 0.35>0.1, and lambda was 6.86 (95% CI, 1.01-12.70). In distinguishing pancreatic adenocarcinoma from chronic pancreatitis, the pooled sensitivity and specificity of telomerase activity were 0.77 (95% CI, 0.61-0.88) and 0.97 (95% CI, 0.91-0.99), respectively; DOR was 117.28 (95% CI, 32.25-426.53); beta was −0.38 (95% CI, −1.89-1.13), Z was −0.49, p was 0.62>0.1, and lambda was 5.30 (95% CI, 3.37-7.24). Conclusions: The present meta-analysis demonstrates that telomerase activity could be a useful biomarker for the differential diagnosis of pancreatic adenocarcinoma and benign pancreatic diseases.